Experiences of Unbelonging and Ableism in the Early Learning and Childcare Sector in British Columbia - Gerlach, Alison J.; Newbury, Janet; Berggren, Tabatha (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2024)
In an era in which Canadian governments are focused on increasing families’ access to affordable early learning and childcare (ELCC), there are increasing concerns about the inclusion of children with disabilities. This paper reports on the experiences of parents of children with disabilities in accessing ELCC programs in British Columbia. Findings highlight four interrelated themes: experiences of unbelonging; systemic mechanisms that reinforce unbelonging; impacts of unbelonging on children, parents, and families; and experiences of inclusion and belonging. The paper concludes with a discussion on opportunities for disrupting structural ableism and reorienting towards a childcare system in which all children can belong.